2010
DOI: 10.1074/jbc.m110.116426
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H2A.X by DNA-dependent Protein Kinase Is Not Affected by Core Histone Acetylation, but It Alters Nucleosome Stability and Histone H1 Binding

Abstract: Phosphorylation of the C-terminal end of histone H2A.X is the most characterized histone post-translational modification in DNA double-stranded breaks (DSB). DNA-dependent protein kinase (DNA-PK) is one of the three phosphatidylinositol 3 kinase-like family of kinase members that is known to phosphorylate histone H2A.X during DNA DSB repair. There is a growing body of evidence supporting a role for histone acetylation in DNA DSB repair, but the mechanism or the causative relation remains largely unknown. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 62 publications
(84 reference statements)
5
41
0
Order By: Relevance
“…Accordingly, it has been reported that promoters of active (or poised) genes are either nucleosome-free or marked with unstable nucleosomes that contain specific histone variants such as H3.3 and H2A.Z [28]. Although H2AX does not affect nucleosome conformation, it has a destabilizing effect that is enhanced by its phosphorylation and results in an impaired linker histone H1 binding [29]. HMGA proteins were shown to dynamically compete with H1 for binding to the linker DNA, thereby loosening the chromatin [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been reported that promoters of active (or poised) genes are either nucleosome-free or marked with unstable nucleosomes that contain specific histone variants such as H3.3 and H2A.Z [28]. Although H2AX does not affect nucleosome conformation, it has a destabilizing effect that is enhanced by its phosphorylation and results in an impaired linker histone H1 binding [29]. HMGA proteins were shown to dynamically compete with H1 for binding to the linker DNA, thereby loosening the chromatin [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of H2AX in nucleosomes has a modest de-stabilizing influence that is enhanced in vitro by DNA-PKmediated phosphorylations at Thr136 and Ser139, resulting in reduced histone H1 binding and reduced compaction [352]. This phosphorylation occurs independently of core histone acetylation.…”
Section: Kap1mentioning
confidence: 98%
“…A recently described site of H2AX C-terminal phosphorylation is Thr136 [352]. The presence of H2AX in nucleosomes has a modest de-stabilizing influence that is enhanced in vitro by DNA-PKmediated phosphorylations at Thr136 and Ser139, resulting in reduced histone H1 binding and reduced compaction [352].…”
Section: Kap1mentioning
confidence: 99%
“…The phosphorylation of histone H2A.X at Ser139 (gH2A.X) marked the sites of DNA lesions caused by irradiation, UV and alkylation agents, and provided a nucleation site for recruitment of DNA damage checkpoint and DNA repair proteins. [20][21][22] Thus, we examined the gH2A.X levels in A549 cells transfected with miR-33b-3p mimics or NC. As the result revealed, A549 cells transfected with miR-33b-3p mimics displayed lower phosphorylated levels of gH2A.X compared with that in NC transfected cells after cisplatin treatment (Fig.…”
Section: Mir-33b-3p Potentially Facilitated Dna Damage Repair Againstmentioning
confidence: 99%